Diffusion and Controlled Release in Physically Crosslinked Poly (Vinyl Alcohol)/Iota-Carrageenan Hydrogel Blends - Croitoru, Catalin; Roata, Ionut Claudiu; Pascu, Alexandru; Stanciu, Elena Manuela (MDPI- Polymers, 2020)
This paper reports the obtaining of poly (vinyl alcohol) and i-carrageenan blend hydrogels by physical crosslinking (consecutive freeze-thaw cycles). The two polymers were completely miscible in the weight ratio interval used in this study, as determined by solution viscometry data. Strong interactions through hydrogen bonding and forming of mixed interpolymer crystalline domains were observed, which are responsible for the formation of stable drug release-tunable matrices. The release profiles of three model antibiotic drugs (amoxicillin, tetracycline hydrochloride, and gentamicin sulfate) were assessed in a pH interval between 3 and 7.3. They were found to be strongly dependent on the drug chemistry, mesh size of the hydrogels, swelling mechanism, and pH of the release medium. A decrease of up to 40% in the release rates and up to 10% in the diffusion coefficients of the model drugs was registered with the increase in i-carrageenan content.
Keywords: controlled release.; hydrogels; iota-carrageenan; poly (vinyl alcohol); polymer blends; polysaccharide; swelling